ANALISIS IMPLEMENTASI SISTEM PROTEKSI PENANGGULANGAN KEBAKARAN PADA KAPAL MOTOR PENUMPANG X - Annisa Putri Pertiwi; Bina Kurniawan; Daru Lestantyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The X Passenger Motor Ship is a type of roll on-roll off (Ro-Ro) ship used for ferry boats by carrying passengers and vehicle cargo. The ship has greatest potential danger to the occurrence of fire which will cause a considerable amount of losses. The X Passenger Motor Ship has been equipped with fire prevention system including fire protection system, life safety facility, and fire management. The purpose of this research is to analyze fire protection system based on Standard Safety of Life at Sea (SOLAS), Biro Klasifikasi Indonesia (BKI) of Rules for The Classification and Construction Standard Seagoing Ships, and National Fire Protection Association (NFPA) at the X Passenger Motor Ship. This research is a qualitative research with observational method and depth interview. The results show that the implementation of fire protection system and life safety facilities are equipped with all requirements of a passenger ship but the need for additional protection equipment and safety facilities in some areas of the ship. While the implementation of fire management has been going well but need the addition of duties and responsibilities on one of the new crew. In this study it can be concluded that the implementation of a good fire protection protection system will improve good fire fighting procedures as well.